1999
DOI: 10.1046/j.1365-2699.1999.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling climate response to historical land cover change

Abstract: Summary In order to estimate the effect of historical land cover change (deforestation) on climate, we perform a set of experiments with a climate system model of intermediate complexity – CLIMBER‐2. We focus on the biophysical effect of the land cover change on climate and do not explicitly account for the biogeochemical effect. A dynamic scenario of deforestation during the last millennium is formulated based on the rates of land conversion to agriculture. The deforestation scenario causes a global cooling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
91
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(110 citation statements)
references
References 21 publications
10
91
3
Order By: Relevance
“…The cooling effect of LUC in winter is more than 1.4˝C. This is mainly attributed to the high albedo values in LUC regions, which is further enhanced via snow-albedo feedback, in agreement with Bonan G. [10], Feddeman et al [17] and Brovkin et al, [16]. As for the summer season, the regions with statistically significant cooling are smaller, with differences in two meter temperature values less than 1.2˝C.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The cooling effect of LUC in winter is more than 1.4˝C. This is mainly attributed to the high albedo values in LUC regions, which is further enhanced via snow-albedo feedback, in agreement with Bonan G. [10], Feddeman et al [17] and Brovkin et al, [16]. As for the summer season, the regions with statistically significant cooling are smaller, with differences in two meter temperature values less than 1.2˝C.…”
Section: Discussionsupporting
confidence: 83%
“…Usually, two simulations, with and without LUC, are performed with global or regional climate model to assess the impact of LUC. Using this methodology, past studies have shown that LUC induces a cooling at the global scale [15][16][17], though there are important differences regionally. LUC is shown to cool temperatures in the high and temperate latitudes of North America, while warming is noted for the tropical latitudes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation exerts a warming influence by (i) adding CO 2 to the atmosphere, (ii) eliminating the possible increased carbon storage in trees as a result of future CO 2 fertilization, and (iii) decreasing evapotranspiration, particularly in the tropics (1-6). However, deforestation also exerts a cooling influence by (iv) decreasing the surface albedo, particularly in seasonally snow-covered high latitudes (7)(8)(9)(10). We will refer to the first two climate effects that are mediated by changes in atmospheric carbon dioxide content as ''carbon-cycle effects'' and refer to the other two climate effects of forests as ''biophysical effects.''…”
mentioning
confidence: 99%
“…Also, a new type of climate model has recently been developed called Earth system models of intermediate complexity (EMICs) (Claussen et al, 2002) which allow the simulation of climate over much longer time periods, including the whole Holocene . These allow the dynamic timedependent response of the atmosphere to be investigated against a variety of internal (ice, ocean circulation, biosphere, trace gases) and external (orbital) forcing mechanisms (Brovkin et al, 1999;Ganopolski and Rahmstorf, 2001;Weber, 2001). Evaluation of these model simulations against actual climate change requires palaeoclimate data at a comparable temporal and spatial scale.…”
Section: Introductionmentioning
confidence: 99%